How flower visitation of remnant grassland patches is affected by commercial timber plantations and an invasive alien species (Rubus cuneifolius) - Hansen, Simone (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.